P16/CDKN2 alterations and pRb expression in oesophageal squamous carcinoma. Issue 2 (April 1998) - Busatto, G; Shiao, Y H; Parenti, A R; Baffa, R; Ruol, A; Plebani, M; Rugge, M
Abstract : BACKGROUND: Upregulation of the cell cycle associated genes, p16/CDKN2 and the retinoblastoma susceptibility gene (Rb), is commonly seen during the proliferation of normal cells. An inverse relation between the expression of p16/CDKN2 and Rb has been noted in many tumours, but has not yet been determined in oesophageal squamous carcinoma. AIMS: To investigate p16/CDKN2 genetic alterations and both the p16/CDKN2 and the Rb protein (pRb) immunophenotypes in oesophageal squamous carcinoma. METHODS: Twenty primary oesophageal squamous carcinomas were examined for mutations in p16/CDKN2 by the polymerase chain reaction, single stranded conformational polymorphism, and DNA sequencing. Synthesis of p16/CDKN2 and pRb proteins was determined by immunohistochemistry in 19 specimens of formalin fixed, paraffin wax embedded tissues. RESULTS: Mutations of p16/CDKN2 were not detected in exons 1 and 2. In only one case, G to C and C to T base changes were detected in a non-coding region of exon 3. Expression of p16/CDKN2 and Rb was observed in both normal and neoplastic areas of tissue sections, indicating neither consistent homozygous deletion nor consistent hypermethylation of the genes in tumours. Fourteen tumours showed an inverse expression of p16/CDKN2 and Rb. An increased percentage of cells that immunostained positively for p16/CDKN2 but not for pRb was observed in eight tumours, five of which had no detectable pRb, suggesting defective Rb expression in these oesophageal squamous carcinomas. CONCLUSIONS: These results indicate that p16/CDKN2 mutations occur infrequently in oesophageal squamous carcinoma. The alteration of the Rb gene is suggested as an important step in the development of these tumours.